Fumarate hydratase deficiency and cancer: activation of hypoxia signaling? - Ratcliffe, P (2007)
Molecular genetic analysis of hereditary leiomyomatosis and renal cell cancer (HLRCC) unexpectedly revealed germline defects in the gene encoding the Krebs cycle enzyme fumarate hydratase (FH), stimulating great interest in the underlying mechanism of oncogenesis. It has been proposed that the associated accumulation of fumarate competitively inhibits the 2-oxoglutarate-dependent dioxygenases that regulate hypoxia-inducible factor (HIF), thus activating oncogenic hypoxia pathways. In this issue of Cancer Cell, Pollard and colleagues describe a genetic mouse model of FH deficiency that recapitulates aspects of the human disease, including HIF activation and renal cysts, enabling further insights into this unusual cancer syndrome.